2022
DOI: 10.3390/life12030376
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study on the Viability of Normal and Cancerous Cells upon Irradiation with a Steady Beam of THz Rays

Abstract: Terahertz (THz) electromagnetic radiation is commonly used in astronomy, security screening, imaging, and biomedicine, among other applications. Such approach has raised the question of the influence of THz irradiation on biological objects, especially the human body. However, the results obtained to date are quite controversial. Therefore, we performed a comparative study on the viability of normal cells and cancer cells upon irradiation with a steady beam of THz rays. We used human peripheral blood mononucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…showed an increased death rate of primary human mononuclear blood cells (monocytes and B-and T cells) upon 0.14 THz irradiation. 37 …”
Section: Discussionmentioning
confidence: 99%
“…showed an increased death rate of primary human mononuclear blood cells (monocytes and B-and T cells) upon 0.14 THz irradiation. 37 …”
Section: Discussionmentioning
confidence: 99%
“…Further, a recent in vivo study suggested that THz radiation increased antidepression, anti-anxiety, and social interactions in exposed mice [ 64 ]. Moreover, THz EMR has been reported to cause death of human primary and malignant cells [ 65 ]. At 3.1 THz, exposure can alter the endocytic process of neuronal cells [ 66 ].…”
Section: Biological Effects Of Microwavesmentioning
confidence: 99%